Aethiology of stem canker pathogen in Jatropha curcas L. in Peninsular Malaysia - Sulaiman, Roslina (2011)
Jatropha curcas is a multipurpose shrub that can be found throughout tropic and subtropic regions. It is a non-edible plant which is mainly cultivated for production of bio-diesel. This plant is not only tolerant to drought and salinity but it is also resistant to pests and diseases. However, new diseases on J. curcas have recently been reported recently and among them is stem canker disease. Stem canker disease caused by Pestalotiopsis sp. has been reported in India. Similar stem canker symptoms have also been observed in Malaysia but no research effort has been taken to identify the causal agent and the effect of the disease on J. curcas production. The purpose of this study was to identify and characterize the causal pathogen of stem canker on J. curcas in Malaysia using morphological and molecular characteristics and to confirm the pathogenicity of the causal agent. The study was carried out in four different phases which started with sampling, isolation, identification and pathogenicity test. Through sampling, the disease incidence was recorded and pure culture was isolated. Identification of pathogen was done through morphology and molecular characterization using Internal Transcribed Spacer (ITS) regions of ribosomal deoxyribonucleic acid (rDNA). The pathogenicity test was then carried out to confirm the pathogenicity of the pathogen on J. curcas. This research found that the disease incidence of stem canker on J. curcas was high, from 10% to 80%. A total of 48 samples of stem with canker symptoms were collected from 8 locations in three states of Malaysia but only 27 isolates were used due to sporulating ability on artificial media. Morphological characterization of pure culture indicated that the colony was fast growing with fluffy white aerial mycelia which eventually turned to black when mature. The fungus conidia were two-celled, dark brown, thin cell walled, oval in shape and have longitudinal striations when mature, whereas immature conidia were hyaline, thick cell walled, smooth and one-celled. The average size of conidia was 23.63 μm (length) x 12.72 μm (width) while the average length/width ratio was 1.86 (n = 200). The morphological findings described the pathogen as Lasiodiplodia theobromae. Additionally, BLAST results indicated that all the 27 sequences were 99% to 100% identical to that of L. theobromae. Phylogenetic tree which grouped the 27 isolates in the same cluster with L. theobromae and distinct from other anamorph in genus Botryosphaeria proved that the isolate that caused stem canker is L. theobromae. The pathogenicity test undertaken using mycelial plugs showed symptoms as canker on J. curcas stem within a week after inoculation. The symptoms development included black necrotic lesions that appear sunken and as cracks on the bark and gradual plant wilting and eventually plant death. The pathogen was successfully re-isolated from lesions of inoculated stems, thus fulfilling Koch's postulates and confirmed that L. theobromae was indeed the causal agent of stem canker in J. curcas in Malaysia.